The new immigration federalism / Pratheepan Gulasekaram, Santa Clara University, School of Law, S. Karthick Ramakrishnan, University of California, Riverside. - Gulasekaram, Pratheepan; Ramakrishnan, S. Karthick (Subramanian Karthick), 1975- (Cambridge University Press, 2015)
Since 2004, the United States has seen a flurry of state and local laws dealing with unauthorized immigrants. Though initially restrictionist, these laws have recently undergone a dramatic shift toward promoting integration. How are we to make sense of this new immigration federalism? What are its causes? And what are its consequences for the federal-state balance of power? In The New Immigration Federalism, Professors Pratheepan Gulasekaram and S. Karthick Ramakrishnan provide answers to these questions using a mix of quantitative, historical, and doctrinal legal analysis. In so doing they refute the popular 'demographic necessity' argument put forward by anti-immigrant activists and politicians. Instead, they posit that immigration federalism is rooted in a political process that connects both federal and subfederal actors: the Polarized Change Model. Their model captures not only the spread of restrictionist legislation but also its abrupt turnaround in 2012, projecting valuable insights for the future.